PENGARUH LATIHAN PLYOMETRICS TERHADAP PENINGKATAN KEMAMPUAN FREETHROW - Ade Frashetya Mahendra; Alex Aldha Yudi; Witarsyah Witarsyah; Sari Mariati (Universitas Negeri Padang, 2020)
Problem in this study is the lack of ability Free throw athletes sons SMA N 12 Padang. The variables in this study are training plyometrics andability free throw. The purpose of this study was to determine the effect oftraining plyometrics on the improvement of theability of free throw male athletes at SMA N 12 Padang. This type of research is a quasi-experimental that aims to see the effect oftraining plyometrics on improvingability Freethrow's. The population in this study were all basketball athletes at SMA N 12 Padang totaling 30 people. Sampling was done by purposive sampling technique, namely male athletes of SMA N 12 Padang as many as 10 people. To obtain research data, theability test was used Free throw. The data obtained were analyzed by using the t test. Based on the results of data analysis, it is known thatexercise plyometrics thishas a significant effect on increasing the ability of free throws. Where theaverage of pre-test theability free throw was 1.9, while the post test increased to 4.1. Then obtained the mean difference test (t test) of tcount 7.09 while ttable 2.26 with a significant level α = 0.05 and n = 10, then tcount > ttable (7.09> 2.26), it can be concluded that there is a significant effect of the form oftraining plyometrics on the improvement ofability free throw in male basketball athletes at SMA N 12 Padang.